PREVALENCE OF TRADITIONAL CARDIOVASCULAR RISK FACTORS FOR CORONARY ARTERY DISEASE AND ELEVATED FIBRINOGEN AMONG ACTIVE MILITARY PERSONNEL IN REPUBLIC OF SERBIA: A CROSS-SECTIONAL STUDY: Traditional risk factors and elevated fibrinogen among active military personnel in Republic of Serbia - Pandrc, Milena Slobodan; Ratković , Nenad; Perić, Vitomir; Stojanović, Maja; Kostovski , Vanja; Rančić, Nemanja (Journal of Medical Biochemistry, 2021)
Background: It is well known that less than 1% of the population achieves ideal cardiovascular health as well as 65% of patients do not have their conventional risk biomarkers under control. The military service has its own particularities that may contribute to the cardiovascular risk . Methods: In order to define the preventive strategy goals, we analyzed the prevalence of traditional cardiovascular risk factors for coronary artery disease and elevated fibrinogen among active military personnel in Republic of Serbia. Results: The cross-sectional study included 738 individuals older than 20 years, mostly between 31 and 40 years old. The mean value of SBP for the whole group was 122.39±9.42 mmHg, and for the DBP 79.94±6.56 mmHg. Among active military personnel 72.7% (533), had prehypertension and 13.8% (101) was hypertensive. Both body mass and BMI index among the observed age subgroups were found to increase with the age of the patients, as well as cholesterol values. HDL cholesterol values ​​also differed statistically significantly between age subgroups, with the proportion of individuals with HDL less than 1.5 mmol / L in all subgroups was about 85%, the only in the 41-50 age group was lower, 76.4%. LDL cholesterol, as well as the proportion of individuals who had LDL ≥3.5, increases with the age of patients, and an identical trend was recorded with triglycerides. With aging, fibrinogen levels increased. Conclusions: Those findings considering cardio and cerebrovascular risk factors would help to create the new approach for primary prevention for these categories of individuals.